Набуття та розпоряджання майновими правами інтелектуальної власності фізичними особами – підприємцями - Дмитришин, Володимир Степанович; Dmutrushun, Volodumur (ВД "Гельветика", 2019)
Досліджено особливості правового механізму набуття, розпоряджання і використання в господарській діяльності фізичними особами – підприємцями об’єктів інтелектуальної власності, особливості співвідношення правового статусу таких осіб та статусу фізичних осіб – авторів таких об’єктів і вплив їхнього правового статусу на правовідносини щодо прав інтелектуальної власності. Проаналізована судова практика та розглянуті особливості окремих видів договорів щодо передання прав на торговельні марки та винаходи.

The legislation of Ukraine stipulates that the legal acts regulating the business activity of legal entities are applied to the entrepreneurial activity of natural persons. However, in practice, enforcement results in the emergence of controversial conclusions, since in some way the merger of the legal status of an individual with a legal status of a legal entity which, for their legal nature is different. This applies to the acquisition, state registration and disposal of property rights intelekual property. A citizen who wishes to exercise his right to entrepreneurial activity, after passing the corresponding registration and other procedures, under no circumstances loses and does not change his status of an individual who he has acquired from the moment of his birth, but only acquires a new sign – “entrepreneur”. The legal status of the "individual entrepreneur" does not affect or limit the civil authority of the person, but in economic relations, physical persons – entrepreneurs take part as entrepreneurs, and not as individuals. An individual acquires intellectual property rights always as solely an individual as such. If a person wants to use these rights in the process of economic activity, the legal mechanisms of such use should be applied based on the purpose of such use. It is the purpose of the use that will influence the legal status of such an object of intellectual property as the object of legal relationship and will determine the content of such legal relationships and the law applied to them The legal status of an individual – an entrepreneur, in its scope is wider than the legal status of physical the person, because it includes not only the last, but also additional rights and obligations of the person in the field of business relations. Accordingly, if the use of the object of intellectual property is carried out within the framework of these additional powers, such use will require appropriate regulatory support, namely, the conclusion of a contract between an individual and an individual entrepreneur on the transfer of rights to the object of intellectual property.
Дмитришин В. С. Набуття та розпоряджання майновими правами інтелектуальної власності фізичними особами – підприємцями / В. С. Дмитришин // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 48-54.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; розпоряджання майновими правами інтелектуальної власності; суб’єкти права інтелектуальної власності; договори щодо розпоряджання правами інтелектуальної власності; disposal of intellectual property rights; subjects of intellectual property rights; treaties of intellectual property rights disputes